Biological Nitrogen Removal via Nitrite by Shortcut Nitrification-Denitrification Process in Sequencing Batch Biofilm Reactor - กฤตสุนันท์กุล, ชาญยุทธ (Progress in Applied Science and Technology, 2018)
A sequencing batch biofilm reactor (SBBR) was operated to remove carbon and nitrogen from synthetic wastewater with a carbon-nitrogen ratio of 5. This reactor was operated sequentially under 4 hours anaerobic and 12 hours aerobic conditions in one cycle. The results showed that 95.42% of COD was removed under anaerobic condition, while 90.68% of ammonium was oxidized under aerobic condition by without nitrite and nitrate accumulation in the effluent. These phenomena were demonstrate by denitrifying glycogen accumulating organism (DGAO) and nitrifying bacteria with coexist in biofilm. The coexistence of these microorganisms resulted in shortcut nitrification-denitrification process in the reactor. Therefore, ammonium was oxidized to nitrite by nitrifying bacteria after that nitrite was utilized as an electron acceptor by DGAO at utilization rate of 0.94 g N/m2-d. However, concentration of nitrite higher than 5.0 mg N/L could inhibit the activity of DGAO.